Development of Criteria And Indicators for Assessing The Methodological Preparedness of Future Primary School Teachers to Use The “Flipped Learning” Model - Hamidova Laylo Kamildjonovna (International Journal on Integrated Education, 2026)
In today's higher pedagogical education system, assessing the readiness of prospective teachers to use innovative educational technologies is one of the key factors in ensuring educational quality. In particular, the widespread implementation of the Flipped Learning model necessitates a scientifically-based determination of the level of methodological preparedness for its use. While existing research primarily highlights the advantages of Flipped Learning technology and its application methodology, the issue of developing criteria and indicators to assess the methodological preparedness of future primary school teachers to use this model has not been sufficiently studied. This article develops the criteria, indicators, and levels for assessing the methodological preparedness of future primary school teachers to use the Flipped Learning model. Methodological preparedness is described based on motivational, cognitive, activity-related, and reflective components, and evaluation indicators for each component are systematized. The developed assessment system was applied during experimental work, and its potential for practical application was analyzed. The research results showed that the proposed assessment criteria allow for a comprehensive determination of the level of methodological preparedness, monitoring of students' developmental dynamics, and the making of scientifically-grounded pedagogical decisions to improve methodological training. This assessment system holds practical significance for monitoring and increasing the effectiveness of the training process for using the Flipped Learning model in pedagogical higher education institutions.